Improving Children’s Concentration Through Graded Puzzle Games in Group B at KB Nurul Huda - Anis Anis; M Arif Syarif H; Andi Ali Kisai (Universitas Negeri Padang, 2026)
This study aims to improve the concentration skills of early childhood students through the use of graded puzzle materials at Nurul Huda Kindergarten. The research design employed was Classroom Action Research based on the Kemmis and McTaggart model, conducted systematically over multiple cyclical phases. Each cycle comprised the integrated stages of planning, implementation, observation, and reflection. The subjects in this study consisted of children in Group B aged five to six years. Data collection was conducted through structured observation and documentation. To ensure a comprehensive measurement basis from the outset, the observation instruments utilized targeted observation sheets designed to systematically track behavioral changes. The measurement was strictly anchored on key concentration indicators, which included the children’s attention span, their persistence in completing tasks, their ability to follow instructions, and their overall engagement in learning activities. The intervention was guided by a predefined success criterion, which mandated that the study would be deemed successful only when a clear majority of the classroom cohort successfully reached the expected and advanced developmental categories. Data analysis used a quantitative descriptive approach to track developmental transformations across the research phases. The results of the study indicate a gradual and consistent improvement in the children’s concentration skills at each stage of the intervention. From the initial pre-cycle baseline condition, the proportion of children reaching the expected developmental categories rose steadily in the first cycle and culminated in meeting the established success criteria during the final cycle. These qualitative behavioral shifts indicate that the progressive difficulty curve embedded within the graded puzzle materials effectively helped children expand their focus, follow teacher instructions more adaptively, and complete structural tasks with greater perseverance while minimizing cognitive boredom. Based on these results, it can be concluded that graded puzzle materials serve as an effective alternative learning strategy to optimize attention control and independent problem-solving skills in young children